The geological economic of sand quarry resources in Jantho, Aceh Besar. Issue 1 (February 2021) - Rais, A; Irham, M; Adrian, F; Deli, A
Abstract: Jantho, the Great Aceh district, is rich in its natural resources, which can benefit people. With the increasing need for humankind to increase minerals in both quantity and type, the knowledge about exploiting minerals into the material of high economic value also increases. Therefore, the research on sand quarry resources' economic potential needs to be carried out to estimate sand resources and their geological economy. This research was conducted in the area of Jantho with the scope of study covering characteristic lithology analysis, calculation of sand resources, and study of geological condition based on field data analysis and data derived from the literature. In estimating the resources, the contour method was used, and for the economic value, the sieve analysis method was employed. The result informed that sand resources are very economical when the sand is classified based on its type and size. The results also show that economically sand resources are four times more profitable when it is categorized based on type and size than when it is sold in the form of no sorting.